2022
DOI: 10.5817/cp2022-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Can mediated communication moderate the relationship between being in isolation and quarantine for COVID-19 and loneliness?

Abstract: An online survey examined if and how aspects of mediated communication were associated with less loneliness while in isolation and quarantine for COVID-19. A national sample of 490 US participants who were either in isolation, quarantine, or in neither, answered questions regarding their use of mediated communication, the people with whom they communicated, perceived social presence, active and passive social media use, and perceived loneliness. SPSS software was used to run a multivariate regression model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Passive MSM use can lead to many negative outcomes. Many studies have found that passive social media use can be related to the feelings of envy (Kashian, 2022), low self-esteem, and other mental health issues; it can trigger an increased social comparison tendency (Ellison et al, 2020) and negatively affect well-being (Yue et al, 2022). If users believe their information on MSM is being recorded, leaked, or spread, they might adopt passive use behavior to protect personal privacy (Teng et al, 2022).…”
Section: Passive Msm Usementioning
confidence: 99%
“…Passive MSM use can lead to many negative outcomes. Many studies have found that passive social media use can be related to the feelings of envy (Kashian, 2022), low self-esteem, and other mental health issues; it can trigger an increased social comparison tendency (Ellison et al, 2020) and negatively affect well-being (Yue et al, 2022). If users believe their information on MSM is being recorded, leaked, or spread, they might adopt passive use behavior to protect personal privacy (Teng et al, 2022).…”
Section: Passive Msm Usementioning
confidence: 99%